Structural changes to primary visual cortex in the congenital absence of cone input in achromatopsia - Molz, Barbara; Herbik, Anne; Baseler, Heidi A.; de Best, Pieter B.; Vernon, Richard W.; Raz, Noa; Gouws, Andre D.; Ahmadi, Khazar; Lowndes, Rebecca; McLean, Rebecca J.; Gottlob, Irene; Kohl, Susanne; et al. (NeuroImage clinical, 2022)
•Anatomy of primary visual cortex (V1) assessed with surface-based morphmetry in those with congenital achromatopsia (ACHM).•Reduction in cortical surface area in foveal, parafoveal and paracentral representations of V1 in those with ACHM.•In ACHM a localized thickening in the area of V1 that represents the region of retina occupied solely by cones.•V1 changes in ACHM may limit its ability to take on normal properties if retinal function were to be restored.•Early intervention, before the development plastic period is over, may offer better restoration of vision in ACHM. Autosomal recessive Achromatopsia (ACHM) is a rare inherited disorder associated with dysfunctional cone photoreceptors resulting in a congenital absence of cone input to visual cortex. This might lead to distinct changes in cortical architecture with a negative impact on the success of gene augmentation therapies. To investigate the status of the visual cortex in these patients, we performed a multi-centre study focusing on the cortical structure of regions that normally receive predominantly cone input. Using high-resolution T1-weighted MRI scans and surface-based morphometry, we compared cortical thickness, surface area and grey matter volume in foveal, parafoveal and paracentral representations of primary visual cortex in 15 individuals with ACHM and 42 normally sighted, healthy controls (HC). In ACHM, surface area was reduced in all tested representations, while thickening of the cortex was found highly localized to the most central representation. These results were comparable to more widespread changes in brain structure reported in congenitally blind individuals, suggesting similar developmental processes, i.e., irrespective of the underlying cause and extent of vision loss. The cortical differences we report here could limit the success of treatment of ACHM in adulthood. Interventions earlier in life when cortical structure is not different from normal would likely offer better visual outcomes for those with ACHM.